NALAR MAZHAB SOSIOLOGIS DALAM PENEMUAN HUKUM YANG BERKEADILAN OLEH HAKIM - Widowati, Christiani; Herliana, Herliana (UI Scholars Hub, 2021)
The issue of justice is a philosophical and contemporary issue. As a philosophical study, justice is examined from several schools of thoughts within the philosophy of law. This study focuses on the sociological jurisprudence discipline which basically states that law as a social norm which is inseparable from the values prevailing in a society because there is a close correlation between law and society. In relation to judicial authority, the denotation of justice in the judge's decision is that it should be in accordance with the law prevailing in the community. This research was conducted through the statute approach method by collecting and analyzing laws and regulations related to the focus of this study, complemented by a conceptual approach based on the legal principles found in the laws and regulations and legal doctrines. Thus, it is perceivable that the sociological jurisprudence is the synthesis of the dialectical studies between normative and positivist views on the legal findings made by judges by interpreting justice as an accord between judges' decisions and legal values living in the society.